Preterm birth, unplanned hospital contact and mortality in infants born to teenage mothers in five countries: a cross-country comparison using linked administrative data. (2018) - Harron, Katie; Verfuerden, Maximiliane; Ibiebele, Ibinabo; Liu, Can; Kopp, Alex; Guttmann, Astrid; Ford, Jane; Hjern, Anders; Meulen, Jan van der; Gilbert, Ruth
No abstract available